Predictive value of the quantitative fetal fibronectin levels for the management of women presenting with threatened preterm labour - A revised cut off level: A retrospective cohort study - Kassam Mahomed; Ibinabo Ibiebele; Christine Fraser; Consuela Brown (Elsevier, 2019)
Objective: To evaluate a new a cut off level of fetal fibronectin as a predictor of birth in women with threatened preterm labour. Design: A retrospective cohort study performed at Ipswich hospital, Ipswich, Queensland, Australia, in women with threatened preterm labour with intact membranes between 23 weeks to 34 + 6 week gestation. Study design: A quantitative fetal fibronectin (fFN) was performed. Maternal demographics and birth outcome data were extracted from the routinely collected perinatal data held by the hospital. The odds of preterm birth were estimated for each cut off value of fFN (10, 50 and 200 ng ml−1) using logistic regression and accounting for multiple presentations by the same woman. Results: Among the 447 presentations and 376 pregnancies, rates of preterm birth <34 weeks were 2.9%, 9.2%, 3.3%, 19.6%, 4.2% and 35.3% for each category of values respectively (fFN <10, ≥10, <50, ≥50, <200 and ≥200 ng ml−1). Birth rates within 7 d of testing were 1.1%, 7.5%, 1.8%, 16.1%, 2.1% and 41.2% respectively. Comparing fFN level of <10 to a level of 10-199 ng ml−1 there was no significant increase in odds of preterm birth < 34 weeks or birth within the next 7 d (OR 2.28, 95% CI 0.84-6.17 and OR 3.61, 95% CI 0.89-14.7 respectively. Conclusion: In women presenting with TPL, those with levels of <200 ng ml−1 have a low risk of birthing within 7 d or before 34 weeks gestation. This allows a personalised decision making and probable discharge home without need for steroid loading. Keywords: Threatened preterm labour, Quantitative fetal fibronectin, Prediction